Introducing Teaching Portfolios in Pre-service English Language Teacher Education in the Teachers’ Training School of Constantine - BELEULMI, Saliha; HAMADA, Hacène (Journal of Human Sciences, 2014)
This article reports on a research project that describes the experience of English language trainees with using teaching portfolios to report and present their learning/teaching experiences during the Practical Training Course (PTC). It aims to illustrate the process of the development of teaching portfolios as a reflective tool for the trainee’s learning/teaching aiming to replace the current training reports used at the Teachers’ Training School of Constantine (TTSC). A procedural study of how the trainees presented the materials and reflected upon them was carried out over a four-month period, as well as their perceptions about the portfolios. Findings from content analysis, reflections and the questionnaire reveal that the teaching portfolio would be a good alternative to report trainees’ learning/teaching experiences and a productive tool to promote reflection and career development.